2021
DOI: 10.15406/ogij.2021.12.00554
|View full text |Cite
|
Sign up to set email alerts
|

Six-year follow-up in patients with urinary stress incontinence treated with Altis® single-incision sling: a prospective single-center study

Abstract: Objetives: Single incision slings are the latest generation of suburethral bands that seek to minimize morbidity and major complications of transobturator bands. In short and medium term, their results in terms of success and safety are similar to transobturator and retropubic bands. Nevertheless, there is little data on their long-term outcomes. Our objective was to evaluate safety and efficacy of Altis® mini-sling during the short, medium and long-term follow-up. Methods: Prospective observational study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…15 Up to the 4-year mark, where the attrition rate was reasonable, negative CST rates ranged between 96.8% and 85.7% from years 1 to 4, respectively. 15 Two publications (same patient cohort) used 24-h Pad Weight Testing, with results of and 90.0% meeting the performance goal of 50% decrease and "dry" (pad weight ≤ 4 gm) measured at 77.2% and 81.1% at 12 and 24 months follow-up respectively. 11,12 Another study that defined cure as pad weight ≤ 8 grams was achieved in 72.0% at 36 months.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…15 Up to the 4-year mark, where the attrition rate was reasonable, negative CST rates ranged between 96.8% and 85.7% from years 1 to 4, respectively. 15 Two publications (same patient cohort) used 24-h Pad Weight Testing, with results of and 90.0% meeting the performance goal of 50% decrease and "dry" (pad weight ≤ 4 gm) measured at 77.2% and 81.1% at 12 and 24 months follow-up respectively. 11,12 Another study that defined cure as pad weight ≤ 8 grams was achieved in 72.0% at 36 months.…”
Section: Discussionmentioning
confidence: 96%
“…20 There were no cases of mesh exposure, extrusion, or erosion due to the study sling observed in the Altis 522 Study, which is consistent with the low event rates described in the literature (0.7−5.2%). [12][13][14][15][16][17][18][19] Interestingly, the first paper published on Altis had an extrusion rate of 3.5%. 12 In that IDE trial there could be no prior experience of the surgeons using Altis since all patients had to be enrolled in the trial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations